Improving Student Science Literacy Skills Through the Use of Teaching Materials with Socioscientific Contexts on Newton's Gravity Material - Saefullah, Asep; Rostikawati, Diana Ayu (Jurnal Pendidikan Fisika, 2024)
This research was motivated by the frequent appearance of news about social issues, such as tidal floods caused by eclipses, which are linked to Newton's theory of gravity. A teaching material was developed that integrated the issue of tidal flooding with physics concepts. The study aimed to determine how scientific literacy among students is influenced by using teaching materials in the context of socioscientific issues. The research methodology was quasi-experimental, utilizing a pretest-posttest design with one group. The study was conducted in the Physics Education Department at Sultan Ageng Tirtayasa University in Serang, Indonesia. The research sample consisted of fifty "Physics Education" majors enrolled in Fundamental Physics I. A scientific literacy test instrument was used as the research tool, and professional validation of the instrument yielded a validation score of 82.45%. The study concluded that teaching materials focused on socioscientific issues related to Newton's theory of gravity positively impacted students' scientific literacy skills. The students' scientific literacy showed an increase of 0.34, categorized as a moderate improvement.